Desafricação e africação na Baixada Cuiabana em Mato Grosso - Justina, Terezinha Della (2021)
This research aims to describe and analyze the phonetic realizations of current alveolopalatal fricatives and dental/alveolar occlusives that can occur as affricates. In the first case, without specifying the vowel or semivowel that form syllables and in the second case, in the position in front of ' i' (vowel, semivowel, or coming from the raising of 'e').Thus, the study focuses on the phonetic-phonological level of the language, observes and describes the foundations of phonetic-phonological theories, with emphasis on Feature Geometry/Autosegmental Phonology - propositions by Clements (1985) and Clements and Hume (1996), Goldsmith (1976, 1990) - especially to understand the assimilation process that involves the realization of dental/alveolar occlusive consonants as alveolopalatal affricates.Data collection took place at two points in Cuiabá: one in a more centralized region and another in a more peripheral region (District of Nossa Senhora da Guia). The two locations are in Baixada Cuiabana, in Mato Grosso. Due to these established geographic borders, the systematization of the characteristic dialectal features of these two contexts is also guided by theoretical principles of dialectology.The research also specifies, with guidance from Labov's Variationist Sociolinguistics (1972/2008), observations of the influence exerted by two intralinguistic factors (voice and stress) and three extralinguistic factors (age, education, gender/sex) so that one variant or the other are introduced.Forty-eight subjects take part of this research, 24 from each location, that are subdivided observing a uniform distribution among these extralinguistic factors. The hypotheses were that in those two places there were two actions in progress in relation to the presence of affricates: those that gave rise to alveolopalatal fricatives in Portuguese were in the process of extinction, being replaced by fricatives and the ones originating from /t, d/ followed of /i, I, y / were in the process of being deployed. The hypotheses were confirmed by the study, but the first process is much more advanced than the second in both places. Some intralinguistic and extralinguistic factors were more favorable than others to the emergence of certain variants: the sonorous voicing is notable for the variables /ʃ, ᴣ/ and the deaf one for /t, d/; but it is the age group that always exerts the greatest influence on changes, because only those who are older still enunciate the current fricatives as affricates, and the occlusive ones follow a gradual process, remaining them almost exclusive in the speech of older people, mixing more the variants in the intermediate, the great absence in the younger people. The level of education and gender/sex, although less prominent, also participate in the occurrences of one or another variant.